Achieving self-enhanced thermal barrier performance through a novel hybrid-layered coating design. (5th April 2019) - Li, Guang-Rong; Wang, Li-Shuang; Yang, Guan-Jun
Abstract: The thermal insulation and durability of thermal barrier coatings (TBCs) are mainly affected by sintering-induced healing of 2D micropores, which is inevitable under high temperature conditions. In this study, we designed and prepared novel hybrid-layered TBCs. During thermal exposure, the degree of degradation in thermal conductivity is observed to decrease from 80 to 100% for conventional coatings to 20% for the novel coatings. For a detailed understanding, the evolution of the hybrid-layered TBCs can be divided into two stages: during stage I (0−10 h), ultrafast healing of 2D micropores occurs, mainly caused by the multiple contacts between the counter-surface. At this stage, the thermal and mechanical properties also increase sharply. During stage II (after 10 h), some new 2D mesopores are formed. Compared with the 2D micropores, the newly formed 2D mesopores have a much larger aspect ratio that increases the ratio of the effective area for thermal insulation from 10 to 30% to 60%, which accounts for the 50% self-enhancement in the thermal barrier performance. This self-enhancing behavior is expected to prolong the lifetime and increase the performance of the TBCs, which is the main objective of using advanced TBCs in next-generation applications. Graphical abstract: Unlabelled Image Highlights: A novel hybrid-layered TBC was prepared by alternate stacking of dense splats and porous nanoheaps. Degree of degradation in thermal conductivity decreases from 80% to 100% for conventional coatings to 20% for novel coatings. Nearly 50% thermal barrier performance is self-enhanced during thermal exposure.